2021
DOI: 10.1016/j.heliyon.2021.e07798
|View full text |Cite
|
Sign up to set email alerts
|

Oversight of bank risk-taking by audit committees and Sharia committees: conventional vs Islamic banks

Abstract: By utilizing the Fixed effect and GMM estimators for a sample of 57 Islamic banks and 102 conventional banks from 10 countries for the period 2002–2018, we examine the effect of the audit committees' and Sharia committees' effectiveness on the bank risk-taking behavior and its transmission mechanisms. The results reveal that an audit committee's independence, number of meetings, and financial expertise negatively affect conventional banks' risk-taking, suggesting that the high effectiveness of their audit comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 80 publications
2
46
0
2
Order By: Relevance
“…It is important because ASEAN, in the near future, is forecasted to be the fifth largest trading region globally, and its weight in the global financial system is increasing. Any adverse shock to the financial sector in these countries may have a contagious effect on other countries due to higher financial openness ( Moudud-Ul-Huq et al., 2018 ; Dang and Nguyen, 2021b ). Moreover, bank risk in these countries can be higher than in developed countries ( Nguyen, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important because ASEAN, in the near future, is forecasted to be the fifth largest trading region globally, and its weight in the global financial system is increasing. Any adverse shock to the financial sector in these countries may have a contagious effect on other countries due to higher financial openness ( Moudud-Ul-Huq et al., 2018 ; Dang and Nguyen, 2021b ). Moreover, bank risk in these countries can be higher than in developed countries ( Nguyen, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the higher the number of SSB the lower the risk-taking behavior of Islamic banks. Similarly, Nguyen [49] study revealed that Sharia committee's high effectiveness can constrain risk-taking behaviors in Islamic banks. All variables, except deposit insurance, are averaged over the period 1992-2008 (or the most available years).…”
Section: Resultsmentioning
confidence: 96%
“…That shows that the multicollinearity of the independent variables is insignificant, and the independent variables in the model are acceptable. (VIF < 10 is acceptable) (Dang & Nguyen, 2021b, 2022Nguyen, 2021b).…”
Section: Regression Model Resultsmentioning
confidence: 99%